Phosphate adsorption in oxisols by humid brushland ( savannah) - Leal, Jair Rocha; Velloso, Ary Carlos X. (Pesquisa Agropecuaria Brasileira, 2014)
Adsorption of phosphate by nine oxisols collected in cerrados (savannah) of São Paulo and Goiás, showed a close relationship with the Langmuir isotherm. Calculated maximum adsorption (25°C; pH 5) for the nine soils varied from 23 to 70 mg P per hundred grams of soil. These maxima are intermediate among values found in the literature for other countries. The adsorption maxima were closely correlated with the amounts of amorphous aluminum oxides (r = 0,867), clay content (r = 0,938) and percentage organic matter (r = 0,922), respectively. Differences in exchangeable alumimum and differences in the amounts of amorphous iron oxides were not correlated with the adsorption maxima.